(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The essays collected here investigate, from various perspectives, the economic impact of rural lordship in Late Medieval Lombardy. In the introduction, the editors offer an overview of the results achieved by the research.